Impacts of Determining Economic Life of Large-Scale Infrastructure Projects on Their Economic Effectiveness - Korytárová, Jana; Hromádka, Vít; Federla, Jakub (Frontiers in Built Environment, 2022)
The paper deals with the refinement of the CBA methodological procedure for the assessment of the economic effectiveness of large-scale transport infrastructure projects. The basic input is economic CF which consists of investment costs, operating income, operating expenses, societal benefits, and harms as well as the investment residual value. According to the methodological guidelines, the currently evaluated project period is considered to be 30 years including the investment phase starting in the first year of the construction, the relevant part of the operational phase, and the residual value of the project in the last year of the assessed period. The evaluation of the economic effectiveness of projects is largely influenced by the determination of the construction economic life. A procedure for calculating the residual value of the project while respecting the gradual implementation of partial constructions was established as part of the research. A case study based on the research sample of several investment construction projects of the highway sections in the Czech Republic demonstrates how this methodological procedure affects the economic effectiveness of the project.